Lhx6 regulates canonical Wnt signaling to control the fate of mesenchymal progenitor cells during mouse molar root patterning. - Jinzhi He (PLoS Genetics, 2021)
Mammalian tooth crown formation has long served as a model for investigating how patterning and morphogenesis are orchestrated during development. However, the mechanism underlying root patterning and morphogenesis remains poorly understood. In this study, we find that Lhx6 labels a subpopulation of root progenitor cells in the apical dental mesenchyme, which is closely associated with furcation development. Loss of Lhx6 leads to furcation and root number defects, indicating that Lhx6 is a key root patterning regulator. Among the multiple cellular events regulated by Lhx6 is the odontoblast fate commitment of progenitor cells, which it controls in a cell-autonomous manner. Specifically, Lhx6 loss leads to elevated expression of the Wnt antagonist Sfrp2 and down-regulation of Wnt signaling in the furcation region, while overactivation of Wnt signaling in Lhx6+ progenitor cells partially restore the furcation defects in Lhx6-/- mice. Collectively, our findings have important implications for understanding organ morphogenesis and future strategies for tooth root regeneration.